Perception of dental fluorosis and other oral health disorders by 12-year-old Brazilian children - MARCELO C. MENEGHIM, FÃƒÆ’Ã‚ÂBIO C. KOZLOWSKI, ANTÃƒÆ’Ã¢â‚¬ÂNIO C. PEREIRA, ANDRÃƒÆ’Ã¢â‚¬Â°A V. AS (IAPD and Blackwell, 2007)
The aim of this study was to verify the perception of dental fluorosis as an oral health problem by 12-year-old Brazilian children and to evaluate if theywere able to detect other oral disorders.